A bola em meio a ruas alinhadas e a poeira infernal: os primeiros anos do futebol em Belo Horizonte, 1904-1921 - Raphael Rajao Ribeiro (2007)
This work focuses on the history of football in Belo Horizonte, between 1904 and 1921, moment of introduction and consolidation of that sport. Aiming to insert the discussion about the capital city of Minas Gerais in the context broader studies relating to the subject above mentioned, in the first chapter there is a bibliographic review of the production about the theme in Brazil. The football, as the first athletic activity to be established in the city, had always been bounded to the development of a sportive field in Belo Horizonte, which is the phenomenon investigated in the course of this work. The links between the development of the athletic environment and the experiences in others centres, specially through the information circulation, also is examined in this study, as well as the relations among the singularities of the capital city of Minas Gerais and the trajectory of the football in its firsts years.